2012
DOI: 10.1063/1.4749256
|View full text |Cite
|
Sign up to set email alerts
|

A novel apparatus for in situ compression of submicron structures and particles in a high resolution SEM

Abstract: We report on the development and characterization of a novel in situ manipulation device to perform stressing experiments on the submicron scale inside a high resolution field emission scanning electron microscope. The instrument comprises two main assembly groups: an upper part for positioning and moving a mounted probe and a force sensor as well as a specimen support as lower part. The upper part consists of a closed loop tripod piezoelectric scanner mounted on a self-locking coarse positioning stage. Two in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 74 publications
0
21
0
Order By: Relevance
“…Also in this case, the E values of 21 and 45 GPa are significantly lower than the value known for bulk fused silica (72-76 GPa) (Adachi and Sakka, 1990). However, they are typical for such SFB-type silica particles, as reported for sol-gel-derived hollow silica spheres and silica microcapsules by Zhang et al (2009Zhang et al ( , 2010 and submicron-sized silica spheres by Romeis et al (2012Romeis et al ( , 2014 and Paul et al (2015), respectively. In difference to this, Romeis et al (2014) and Paul et al (2015) reported E values of 71 ± 1.4 GPa for heat-treated SFB-type silica spheres approaching the values known for bulk fused silica (72-76 GPa) (Adachi and Sakka, 1990).…”
Section: Membranes In the Temmentioning
confidence: 98%
See 2 more Smart Citations
“…Also in this case, the E values of 21 and 45 GPa are significantly lower than the value known for bulk fused silica (72-76 GPa) (Adachi and Sakka, 1990). However, they are typical for such SFB-type silica particles, as reported for sol-gel-derived hollow silica spheres and silica microcapsules by Zhang et al (2009Zhang et al ( , 2010 and submicron-sized silica spheres by Romeis et al (2012Romeis et al ( , 2014 and Paul et al (2015), respectively. In difference to this, Romeis et al (2014) and Paul et al (2015) reported E values of 71 ± 1.4 GPa for heat-treated SFB-type silica spheres approaching the values known for bulk fused silica (72-76 GPa) (Adachi and Sakka, 1990).…”
Section: Membranes In the Temmentioning
confidence: 98%
“…In the present study, the PI95 holder was operated under displacement control, while experiments are carried out with and without e-beam irradiation. In our previous studies on nanoscale silica spheres, we noticed a strong impact of e-beam irradiation on their mechanical behavior inside the TEM (Mačković et al, 2014 and SEM (Romeis et al, 2012). Similarly, in the present work, the impact of e-beam irradiation was investigated in case of silica glass.…”
Section: In Situ Tensile Testing In the Temmentioning
confidence: 99%
See 1 more Smart Citation
“…Uniaxial compression of the single silica particle is performed by a SEM supported in situ manipulator [23]. After a transfer and alignment procedure, ex situ Raman spectroscopy gives access to the local structure of the deformed glass particle [13]: significant densification (about 11%) is found near the deformed contacts; the inner parts of the particle are essentially non-densified.…”
Section: Introductionmentioning
confidence: 99%
“…Particle compression in the SEM supported micromanipulator [23] was performed between a diamond flat punch indenter and a (100) silicon wafer. The displacement rate of the indenter was 200 nm/s; force-and deformation resolutions were 1-10 lN and 5 nm.…”
Section: Introductionmentioning
confidence: 99%